Sperm quality and fertility in rats after prenatal exposure to low doses of TCDD: A three-generation study - Sanabria, Marciana [UNESP]; Cucielo, Maira Smaniotto [UNESP]; Guerra, Marina Trevizan [UNESP]; dos Santos Borges, Cibele [UNESP]; Banzato, Thais Petrochelli [UNESP]; Perobelli, Juliana Elaine [UNESP]; Leite, Gabriel Adan Araújo [UNESP]; Anselmo-Franci, Janete Aparecida; De Grava Kempinas, Wilma [UNESP] (Elsevier, 2016)
Exposure to Tetrachlorodibenzo-p-dioxin (TCDD) in male rats promotes, decreased sperm concentration, alterations in motility and in sperm transit time. We evaluated the effect transgenerational of in utero exposure to low doses TCDD in the sperm quality. Pregnant rats (F0) were exposed to 0.1; 0.5 and 1.0 μg of TCDD, on gestational day 15, coincides with the end of most organogenesis in the fetus. Adult male offspring (F1, F2 and F3 generation) were investigated for fertility after artificial insemination in utero. After collection of the uterus and ovaries, the numbers of corpora lutea and implants were determined. TCDD provoked alterations in sperm morphology and diminution in serum testosterone levels and sperm transit time in the cauda epididymis. The fertility significantly decreased in all the generations, at least at one dose. In conclusion, TCDD exposure decreases rat sperm quality and fertility in adult male offspring and this effects persist into the next generation.
Keywords: Dioxin; Epididymis; Fertility; Sperm quality; Transgenerational effect